Erinacine A-Enriched Hericium erinaceus Mycelium Produces Antidepressant-Like Effects through Modulating BDNF/PI3K/Akt/GSK-3β Signaling in Mice - Chiu, Chun-Hung; Chyau, Charng-Cherng; Chen, Chin-Chu; Lee, Li-Ya; Chen, Wan-Ping; Liu, Jia-Ling; Lin, Wen-Hsin; Mong, Mei-Chin (International journal of molecular sciences, 2018)
Antidepressant-like effects of ethanolic extract of Hericium erinaceus (HE) mycelium enriched in erinacine A on depressive mice challenged by repeated restraint stress (RS) were examined. HE at 100, 200 or 400 mg/kg body weight/day was orally given to mice for four weeks. After two weeks of HE administration, all mice except the control group went through with 14 days of RS protocol. Stressed mice exhibited various behavioral alterations, such as extending immobility time in the tail suspension test (TST) and forced swimming test (FST), and increasing the number of entries in open arm (POAE) and the time spent in the open arm (PTOA). Moreover, the levels of norepinephrine (NE), dopamine (DA) and serotonin (5-HT) were decreased in the stressed mice, while the levels of interleukin (IL)-6 and tumor necrosis factor (TNF)-α were increased. These changes were significantly inverted by the administration of HE, especially at the dose of 200 or 400 mg/kg body weight/day. Additionally, HE was shown to activate the BDNF/TrkB/PI3K/Akt/GSK-3β pathways and block the NF-κB signals in mice. Taken together, erinacine A-enriched HE mycelium could reverse the depressive-like behavior caused by RS and was accompanied by the modulation of monoamine neurotransmitters as well as pro-inflammatory cytokines, and regulation of BDNF pathways. Therefore, erinacine A-enriched HE mycelium could be an attractive agent for the treatment of depressive disorders.